Experimental Study: Avocado Seed Powder as Adsorbent for Fe Metal Ions in Water - Bob Widodi; Suparno; Wipsar Sunu Brams Dwandaru (Universitas Pendidikan Ganesha, 2025)
Heavy metal waste pollution such as iron (Fe) has affected many clean water sources in Indonesia, so alternative solutions are needed to clean them, one of which uses adsorbents from avocado seeds. This study aims to determine the effect of avocado seed powder mass as an adsorbent on Fe metal levels in water and compare the effectiveness of adsorbents activated with HCl and H₂SO₄ solutions. The research method uses an experimental method which includes making adsorbent powder, activation process using HCl and H₂SO₄ solution of 1M concentration, adsorption process, testing with Atomic Absorption Spectroscopy (AAS), and data analysis through tables and graphs. The results showed that HCl adsorbent reached the highest capacity and effectiveness at a mass of 1 gram with an adsorbed Fe content of 7.83 mg/L and an effectiveness of 78.3%, while H₂SO₄ adsorbent reached the highest capacity at a mass of 5 grams with an adsorbed Fe content of 8.09 mg/L and an effectiveness of 80.9%. On average, H₂SO₄ adsorbent has a higher effectiveness (78.2%) than HCl (75.6%). In conclusion, although the addition of adsorbent mass affects the level of Fe adsorbed, the effect is not always linear, and adsorbents activated with 1M H₂SO₄ proved more effective than those activated with 1M HCl.